2014
DOI: 10.1016/j.ophtha.2013.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Optical Coherence Tomography Ganglion Cell–Inner Plexiform Layer Thickness Measurements in Early Glaucoma

Abstract: The binary or-logic combination of minimum GCIPL and average RNFL or rim area provides better diagnostic performances than those of and-logic combinations or best single GCIPL, RNFL, or ONH parameters. This finding may be clinically valuable for the diagnosis of early glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 21 publications
6
70
2
5
Order By: Relevance
“…Abnormal thinning in GCIPL analysis was found in 2/23 (9 %) and 7/23 (30 %) of these eyes for average and minimum measurements, respectively. Similarly, Mwanza et al have reported that among GCIPL parameters, the minimum had the best diagnostic performance in early glaucoma [22]. A discrepancy between GCIPL and RNFL was found in 6/23 (26 %) of the eyes with buried ONHD, with abnormal GCIPL exams and normal RNFL thicknesses.…”
Section: Discussionmentioning
confidence: 88%
“…Abnormal thinning in GCIPL analysis was found in 2/23 (9 %) and 7/23 (30 %) of these eyes for average and minimum measurements, respectively. Similarly, Mwanza et al have reported that among GCIPL parameters, the minimum had the best diagnostic performance in early glaucoma [22]. A discrepancy between GCIPL and RNFL was found in 6/23 (26 %) of the eyes with buried ONHD, with abnormal GCIPL exams and normal RNFL thicknesses.…”
Section: Discussionmentioning
confidence: 88%
“…The RS-3000 SD-OCT has the normative databases of macular GCC thickness, whereas some other SD-OCT instruments CI confidence interval, mGCC macular ganglion cell complex a defined as a glaucomatous eye with MD values of>−6 dB b the regular normative database is for eyes with axial length < 26 mm, and the long axial length normative database is for eyes with axial length between 26 and 29 mm c these two types of significance map for mGCC in 9-mm diameter are shown in Figs. 1 and 2 d classified as abnormal if at least 1 sector of the S/I or GChart flagged < 1 % (red color coding) embed normative databases of ganglion cell layer plus inner plexiform layer (GCL/IPL, GCLplus or GCIPL) thickness for evaluating the RGC-associated retinal layer thickness [41][42][43][44]. The built-in program of the RS-3000 SD-OCT instrument can also provide the GCIPL thickness semi-automatically, but it does not have a normative database of the GCIPL thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Minimum mGCIPL thickness is calculated from a radial line macula scan by sampling 360 spokes of measurements extending from the center of the fovea and selecting the spoke with the lowest average thickness (Mwanza et al, 2012). Combining information from macular and optic nerve head scans may also improve the ability to detect early disease, as an abnormality on either could be indicative of glaucoma (Mwanza et al, 2014).…”
Section: Imaging the Maculamentioning
confidence: 99%
“…1), confocal scanning laser ophthalmoscopy (CSLO), and scanning laser polarimetry (SLP), that obtain objective quantitative measurements of ocular structure and can detect glaucoma at an earlier stage (Chang et al, 2009;Greaney et al, 2002;Huang et al, 1991;Leung et al, 2009Leung et al, , 2010Medeiros et al, 2004bMedeiros et al, , 2005bMedeiros et al, , 2008Mwanza et al, 2012;Naithani et al, 2007;Weinreb et al, 2014;Wollstein et al, 1998Wollstein et al, , 2000Zangwill et al, 2001). In addition to evaluating the optic nerve head and RNFL, imaging devices have also recently been used to evaluate inner layers of the glaucomatous macula Mwanza et al, 2012Mwanza et al, , 2014. Novel strategies for testing visual function have also been introduced, and there has been progress in the development of methods of combining information from structural and functional tests to reduce the noise inherent in biological measurements and better detect genuine pathology Russell et al, 2012).…”
mentioning
confidence: 99%